PEMANFAATAN LAHAN TIDUR DI BAWAH TEGAKAN HUTAN RAKYAT DENGAN TANAMAN NILAM - Titin Handayani (Jurnal Teknologi Lingkungan, 2007)
The agroforest region is bestowed with diverse agro-climatic zones, whichmakes itself a rich storehouse of different types of Flora and Fauna.Besides, this conditions help in introduction, acclimatization, andcultivation of a number of aromatic plants with minimum efforts. Thereare a few commercial crops, which can be cultivated without disturbingthe existing flora and have the potential to establish as cash crops inthis region.Patchouli (Pogostemon cablin) has been identified as one such essentialoil bearing aromatic plant with immense export potential. Patchouli oilproduction could be a rural based, labour intensive, low cost agro-basecottage industry, which will give large-scale employment in rural and hillyareas. Patchouli, being a shade loving plant can easily be grown as anintercrop amidst fruit trees, arecanut, and coconut plantation etc. It canalso be easily cultivated in flood free fallow or wastelands. This will providesome extra income for the farmers. Following figures clearly indicatesthat Patchouli cultivation can be a good option besides the traditionalcrops.